The Efficient Cook: The Upper Lakes & St. Lawrence Transportation Company’s Cookery Manual - Malcomson, Thomas (The Northern Mariner / Le marin du nord, 2025)
Research into the preparation and cooking of food aboard lake freighters is wanting. This article explores the Cookery Manual created for the ships’ cooks in the Upper Lakes and St. Lawrence Transportation Company, in the late 1940s. The manual’s goal was to provide nutritious, tasty meals contributing to the physical and mental health, contentment and efficiency of the company’s crews. The manual is described and four potential sources of inspiration for such a resource are considered. The potential sources include, the Canadian Government nutrition program at the end of the Depression and through World War II; the navy cookbooks in use during the war; cookbooks for the land based cook; and the labour/management relations after the war. All four likely contributed to the Cookery Manual’s development. Much remains to be discovered about food and cooking aboard ships.